Deterioration and Cavity of Surrounding Rocks at the Bottom of Tunnel Under the Combined Action of Heavy-Haul Load and Groundwater: An Experimental Study - Li, Zheng; Chen, Kunping; Li, Ziqiang; Huang, Weiwei; Wang, Xinsheng (Frontiers in Earth Science, 2021)
In China, the first tunnel was built in accordance with the 30-ton heavy-haul railway standard. Based on the change in water and soil pressure obtained from long-term on-site monitoring, the cavity mechanism of the surrounding rock at the bottom of a heavy-haul railway tunnel under rich water conditions was explored in this study. The cavity characteristics and degradation depth of the three types of surrounding rock under different axial loads and hydrodynamic pressures were analyzed through laboratory tests. The structural defects at the bottom of the tunnel and local cracks in the surrounding rock were determined to provide a flow channel for groundwater. The dynamic load of heavy-haul trains causes groundwater to exert high hydrodynamic pressure on the fine cracks. The continuous erosion of the bottom surrounding rock leads to a gradual loss of surrounding rock particles, which would further exacerbate with time. The cohesive soil surrounding rock is noticeably affected by the combined action of heavy-haul load and groundwater in the three types of surrounding rock, and the surrounding rock cavity is characterized by overall hanging. In the simulation experiment, the particle loss of the surrounding rock reached 1445 g, which is 24.2% higher than that of the pebble soil surrounding rock and 40.8% higher than that of sandy soil surrounding rock. The findings of this study could be helpful for developing methods for defect prediction and treatment of heavy-haul railway tunnels.